2003
DOI: 10.1046/j.1365-2427.2003.01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus cycling and partitioning in an oligotrophic Everglades wetland ecosystem: a radioisotope tracing study

Abstract: Summary 1. Our goal was to quantify short‐term phosphorus (P) partitioning and identify the ecosystem components important to P cycling in wetland ecosystems. To do this, we added P radiotracer to oligotrophic, P‐limited Everglades marshes. 32PO4 was added to the water column in six 1‐m2 enclosed mesocosms located in long‐hydroperiod marshes of Shark River Slough, Everglades National Park. Ecosystem components were then repeatedly sampled over 18 days. 2. Water column particulates (>0.45 μm) incorporated radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 58 publications
4
61
1
1
Order By: Relevance
“…sources from coastal ocean water, terrestrial runoff and groundwater, atmospheric deposition), much of the variation in soil storage of phosphorus is due to variation in the carbonate-bound P pool (Zhang et al 2004), even though short-term P storage occurs in organic plant and periphyton pools (McCormick et al 1996;Dodds 2003;Noe et al 2003). …”
Section: Resultsmentioning
confidence: 99%
“…sources from coastal ocean water, terrestrial runoff and groundwater, atmospheric deposition), much of the variation in soil storage of phosphorus is due to variation in the carbonate-bound P pool (Zhang et al 2004), even though short-term P storage occurs in organic plant and periphyton pools (McCormick et al 1996;Dodds 2003;Noe et al 2003). …”
Section: Resultsmentioning
confidence: 99%
“…In the wetlands of the FCE, detritus is expected to play a dominant role in carbon and energy flows. Noe et al (2003) found that floc is a strong regulator of phosphorus cycling in this oligotrophic environment. Noe et al (2002) tested the response of several ecosystem components to continuous, low-level phosphorus additions.…”
Section: Introductionmentioning
confidence: 95%
“…In the Everglades, floc has been defined as a heterogeneous mixture containing senescing periphyton, decaying macrophyte tissue, soil particles, algae and bacteria (DeBusk et al, 2001;Noe et al, 2003). A biomarker-based study by showed that floc composition in the FCE is regulated regionally by local vegetation inputs, particularly from periphyton, emergent and submerged plants and terrestrial plant detritus such as mangroves.…”
Section: Introductionmentioning
confidence: 99%
“…In oligotrophic ecosystems, such as Everglades wetlands, nutrients are often found immobilized in organic forms and are quickly recycled following remineralization , Noe et al 2003). Thus, mobile organic compartments of these ecosystems provide a means by which nutrients can be transported across the landscape.…”
Section: Everglades Detritus As a Nutrient Vectormentioning
confidence: 99%
“…Nutrients therefore spend little time in inorganic forms in oligotrophic ecosystems, such as the extremely phosphorus (P)-deficient Taylor River estuary . Several studies have linked Everglades floc organic matter (OM) to local wetland primary producers , including periphyton , Noe et al 2003, a complex associate of algae, bacteria, and fungi abundant throughout the Everglades, and submerged aquatic vegetation, particularly free-floating bladderwort (Utricularia spp. ;…”
Section: Everglades Detritus As a Nutrient Vectormentioning
confidence: 99%